Prospects of diabetes registry and standard care at primary health facilities in Nigeria: experiential note - Ndubueze, Pleasant C.; Igumbor, Eunice O.; Agofure, Otovwe; Okwelum, Anthonia C.; Ozuem, Prince C.; Nwose, Ezekiel U. (International Journal Of Community Medicine And Public Health, 2019)
Background: As part of the series to advance diabetes register, the aim of this piece of the project was to evaluate the development of a diabetes register at primary healthcare (PHC) level in Delta State Nigeria. This is with a view to determine the PHC capacity for diabetes services. Methods: This clinical observational study was carried out in Novena University health centre in Ukwani Local Government Area and Ogume primary health centre in Ndokwa West Local Government Area, Delta State. A community-based screening was carried out in three communities of Amai, Ezionum and Ogume in July to September 2018, after which a diabetes registers were developed in Novena University health and Ogume primary health centres. Cases of probable diabetes were identified during screening and entered into the diabetes register being developed, which formed the sampled population (n=42). The data were analysed using Microsoft Excel Data Analysis ToolPak 2010. Results: Glucometer, stethoscope and sphygmomanometer were the most available equipment at the two facilities. Medical records of patients were incomplete with 81% missing home addresses and 62% did not have phone numbers. Others records such as date of entry, height, weight and type of diabetes were not recorded. The study also showed 35% prevalence of hypertension in diabetes cases. Conclusions: There is capacity to run diabetes screening and service clinic at the primary healthcare levels, but the limitation was incomplete patient information in the medical records. In development of a diabetes registry at the primary healthcare level, the study recommends comprehensive patients’ documentation during screening and routine medical check-up.